2005
DOI: 10.1002/mabi.200500081
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Microwave‐treated Carboxymethyl Chitin and Carboxymethyl Chitosan Films for Potential Use in Wound Care Application

Abstract: CM-chitin and CM-chitosan films were successfully crosslinked by microwave treatment. Crosslinking of the microwave-treated CM-chitin films involved mainly the carboxylate and the secondary alcohol groups, while crosslinking of microwave-treated CM-chitosan films involved the carboxylate and the amino groups. In addition, the crystallinity of CM-chitin increased with increasing microwave treatment time, whereas an increase in the crystallinity of the microwave-treated CM-chitosan films was not observed. At a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…For example, it has been shown for osteoblast precursor cells that amorphous hydroxyapatite substrates enhanced initial cell attachment compared to highly crystalline hydroxyapatite [5, 6]. In addition, it was reported that fibroblast attachment decreased when a more crystalline carboxymethyl-chitin membrane was used instead of a less crystalline carboxymethyl-chitosan film as the culture substrate [7]. Polymer surface crystallinity was also found to affect the endochondral ossification of rabbit articular cartilage chondrocytes [8].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown for osteoblast precursor cells that amorphous hydroxyapatite substrates enhanced initial cell attachment compared to highly crystalline hydroxyapatite [5, 6]. In addition, it was reported that fibroblast attachment decreased when a more crystalline carboxymethyl-chitin membrane was used instead of a less crystalline carboxymethyl-chitosan film as the culture substrate [7]. Polymer surface crystallinity was also found to affect the endochondral ossification of rabbit articular cartilage chondrocytes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Also optimum conditions for the production of CM-chitin (with MW = 4.11 × 10 6 Da, viscosity = 1926 cP and DA = 45%) were found to be 60% NaOH concentration at 35-40 • C reaction temperature. The effect of DS of insoluble CM-chitin on the calcium uptake has been investigated and it was concluded that CM-chitin may be useful as a platform for in vivo calcification (Wan, Khor, Wong, & Hastings, 1996) .The suitability of CM-chitin as material for biomedicine particularly in wound healing applications (Wongpanit et al, 2005) and as bioactive bone repairing material has also been shown (Kokubo et al, 2004).…”
Section: Carboxymethyl Chitinmentioning
confidence: 96%
“…The potential application of microwave treated CM-chitin and CM-chitosan based films for wound care have been tested (Wongpanit et al, 2005). The in vitro study of 1-ethyl-3(3-dimethylaminopropyl) carbodiimide hydrochloride cross linked (2007) OCM-chitosan Cholesterol The size of novel self aggregated cholesterol succinyl-O,CM-chitosan could be controlled by DS of cholesterol moiety.…”
Section: Carboxymethyl Chitosan In Wound Healing Applicationsmentioning
confidence: 99%
“…It is unique basic polysaccharide in nature because of presence of amino group NH2 in its backbone. It is apolymer of ␤-(1, 4) linked-2-amino-2-deoxyd-glucopyranose derived by N-deacetylation of chitin, abundant naturally occurring polysaccharide with annual production very near the levels of cellulose which consists of mainly ␤-(1-4)-2-deoxy-d-glucose units in aqueous alkaline medium [19][20][21][22]. It occurs in marine invertebrates and shells of marine crustaceans i.e.…”
Section: Introductionmentioning
confidence: 99%